Methodologies for training detection dogs and scent sample storing - Clern, Rebecka (SLU/Dept. of Clinical Sciences (until 231231), 2022)
Dogs’ spectacular sense of smell has been used as a detection tool by humans in many areas. Their olfaction was first used as a hunting tool, but dogs’ detection skills have been shown to also be applicable in, for example, detection of drugs, explosives, and firearms as well as disease detection. Different types of disease detection are possible due to the body’s ability to produce volatile organic compounds (VOCs), which reflect the metabolic state of the body. Many illnesses have been shown to cause the body to produce a distinct pattern of VOCs, and these molecules together make up a specific smell. Sweat is a major source of VOCs, therefore sweat samples are used for disease detection by dogs. The first aim of this study was to examine what track design is most beneficial for detection dogs’ learning. This was done through evaluating the performance of two trained detection dogs in three different track shapes, when training the ability to detect individuals infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) through sweat samples. All tracks consisted of six consoles. In Track 1 the consoles were positioned in a straight line, Track 2 was a circular track, and in Track 3 the six consoles were placed in a slightly curved line. The track design was changed when the trainers discovered risk factors that could potentially lead to false results. The design of the straight track caused the dogs to have a high level of curiosity which subsequently made them skip the first couple of consoles in many searches. The design of the circular track made it possible for the dogs to pick up on visual cues the handlers were unaware of. Both dogs’ sensitivity was the highest in the first track (96.4% and 97.8% respectively), and the lowest in the third track (62.9% and 82.6%). The sensitivity for Track 2 was 78.9% and 85.1%. Similarly, the specificity was also the highest in the first track (99.3% and 99.8%) and the lowest in the third track (94.3% and 98.5%). The specificity for Track 2 was 96.6% and 99.2%. However, the results may have been influenced by prerequisites that differed between the tracks, which makes the results difficult to interpret. The second aim of the study was to examine if Falcon centrifuge tubes are suitable as storage containers for scent samples. This was tested through keeping 50 sealed Falcon tubes together in a freezer for one week, out of which three contained pieces of natural rubber that give off a particular smell. Three detection dogs trained to detect that smell searched through all sealed tubes. The results of the study indicate that the scent did not escape the sealed containers as no dog could detect the scent. Falcon tubes are therefore a promising alternative for storing scent samples since scent contamination between samples would not be possible if the containers do not leak the scent. Further studies would be valuable as this could potentially facilitate storing scent samples in a spaceefficient way. Keywords: detection dogs, scent training, canine scent detection, search dogs, scent samples in a spaceefficient way.